Release of tumor necrosis factor-α and prostanoids in whole blood cultures after in vivo exposure to low-dose aspirin - Ilse Beckmann; Shlomo Ben-Efraim; Monica Vervoort; Henk C. S. Wallenburg (Mediators of Inflammation)
Background: The preventive effect of low-dose aspirin in cardiovascular disease is generally attributed to its antiplatelet action caused by differential inhibition of platelet cyclooxygenase-1. However, there is evidence that aspirin also affects release of inflammatory cytokines, including tumor necrosis factor-α (TNF-α). It is not known whether this is caused by direct action on the cytokine pathway or indirectly through cyclooxygenase inhibition and altered prostanoid synthesis, or both.